The effect of nutrition education with booklet media on knowledge about diet in patients with hypertension - Manalu, Mincu; Hasibuan, Muktamar Ahamadi (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Hypertension is a worldwide public health disease today. Low knowledge about diet can risk an increase in blood pressure in hypertensive patients. This study aims to determine the effect of nutrition education with booklet media on knowledge about diet in patients with hypertension. The research design used was a quasy experiment with a non-randomized one-group pretest-posttest design. This research was conducted at the Lubuk Pakam Health Center. The research time starts from November-December 2023. The subjects of this study were all hypertensive patients in the Lubuk Pakam Health Center work area, as many as 202 people. The sample size was obtained from as many as 66 people using a purposive sampling technique. The inclusion criteria for research samples are hypertensive patients aged 40-60 years and subjects willing to become respondents. Data was collected through questionnaires and a Food Frequency questionnaire (FFQ). Data were analyzed using the T-paired test. The results showed that the mean value of knowledge of hypertensive patients about diet before being given nutrition education with booklet media was 46.9, with an SD value of 17.05. Still, after being given nutrition education with booklet media, it was 69.7, with an SD value of 12.5. Providing education through booklet media is significant to the knowledge score of hypertensive patients about diet. The study concludes that booklet media can contribute to increasing the knowledge score of hypertensive patients when choosing the ingredients and types of food they consume.